Integration of Islamic Values in the Ningkuk Ritual: A Model of Character Education Based on Local Wisdom in South Sumatra - Syarnubi; Septia Fahiroh; Ahmed J. Obaid (MUSLIM HERITAGE, 2025)
This study aims to reveal the moral values contained in the Ningkuk ritual and how these values are instilled in young women in the Sukarami Village community. In addition, this study explains the function of Ningkuk as a model of non-formal character education based on local wisdom and assesses its relevance to the development of national character education. This study examines the integration of Islamic values in the Ningkuk ritual as a model of character education based on the local wisdom of the Sukarami Village community in South Sumatra. Using an ethnographic approach, this study collected data through participatory observation, in-depth interviews, and cultural documentation. The results show that the Ningkuk ritual contains Islamic character values, including birrul walidain, gratitude, patience, cooperation (ta'awun), social solidarity (ukhuwah), manners, responsibility, and spirituality. These values are internalized not through verbal instruction but through social practices, cultural symbols, and intergenerational inheritance mechanisms. This study fills a gap in research that has so far overlooked how Islamic values are substantively integrated into the Ningkuk procession, and how this ritual can be reconstructed into a contextual character education model that is compatible with national education policy. This study concludes that Ningkuk is an authentic pedagogical resource that has strategic relevance for formal and non-formal education, especially in the development of local content curricula and culture-based character building programs. These findings offer a theoretical and practical framework for the integration of Islamic values and local wisdom in the design of character education in Indonesia.   Abstrak Penelitian ini bertujuan untuk mengungkap nilai-nilai moral yang terkandung dalam ritual Ningkuk dan bagaimana nilai-nilai tersebut ditanamkan pada perempuan muda di komunitas Desa Sukarami. Selain itu, penelitian ini menjelaskan fungsi Ningkuk sebagai model pendidikan karakter non-formal berdasarkan kebijaksanaan lokal dan mengevaluasi relevansinya terhadap pengembangan pendidikan karakter nasional. Penelitian ini mengkaji integrasi nilai-nilai Islam dalam ritual Ningkuk sebagai model pendidikan karakter berdasarkan kebijaksanaan lokal komunitas Desa Sukarami di Sumatera Selatan. Dengan pendekatan etnografis, penelitian ini mengumpulkan data melalui observasi partisipatif, wawancara mendalam, dan dokumentasi budaya. Hasil penelitian menunjukkan bahwa ritual Ningkuk mengandung nilai-nilai karakter Islam, termasuk birrul walidain, rasa syukur, kesabaran, kerja sama (ta'awun), solidaritas sosial (ukhuwah), sopan santun, tanggung jawab, dan spiritualitas. Nilai-nilai ini diinternalisasi bukan melalui instruksi verbal, melainkan melalui praktik sosial, simbol budaya, dan mekanisme pewarisan antar generasi. Penelitian ini mengisi kekosongan dalam penelitian yang hingga kini belum memperhatikan bagaimana nilai-nilai Islam secara substansial diintegrasikan ke dalam prosesi Ningkuk, serta bagaimana ritual ini dapat direkonstruksi menjadi model pendidikan karakter kontekstual yang sesuai dengan kebijakan pendidikan nasional. Studi ini menyimpulkan bahwa Ningkuk merupakan sumber pedagogis autentik yang memiliki relevansi strategis bagi pendidikan formal dan non-formal, terutama dalam pengembangan kurikulum konten lokal dan program pembentukan karakter berbasis budaya. Temuan ini menawarkan kerangka teoretis dan praktis untuk integrasi nilai-nilai Islam dan kebijaksanaan lokal dalam desain pendidikan karakter di Indonesia.